From ritual to god in the ancient Near East: tracing the origins of religion - Laneri, Nicola (Cambridge University Press, 2024)
"This book traces the transformation of the belief systems that shaped life in ancient Near Eastern communities, from prehistoric times until the advent of religious monotheism in the Levant during the first millennium BCE. It offers new insights into the symbolic value embodied in the religious materiality produced in the ancient Near East"--